El discurso oficial sobre la Universidad - Galcerán, Montserrat (Logos. Anales del Seminario de Metafísica, 2003)
The article discusses the so-called university crisis showing that, simultaneously to this crisis and the unstructuring process, we are facing a reconversion of the institution on the frame of the contemporary information society that models it as a potential enterprise. Nowadays, universities are being inserted in the cognitive capitalism, which makes a business activity out of the production of knowledge, thus subjected to every mechanism of capitalist production and dependent of the marketing of its items/services. As a conclusion, the article reviews the various strategies displayed to face the university crisis: the official strategies of the academic institutions, the proposals of the teaching profession and the student's proposals; each of them analyses this process from different.
Keywords: University; University crisis; Cognitive capitalism; Knowledge marketing; University and information society; Educational strategies